2014
DOI: 10.1002/crat.201300388
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic composition and morphology of calcium carbonate as a function of ultrasonic irradiation

Abstract: This paper reports on the precipitation of CaCO 3 polymorphs, having various crystal morphologies under different conditions. In particular, systems that were subject to ultrasonic irradiation were compared to the corresponding reference systems in the absence of such a treatment. The application of ultrasonic irradiation predominantly resulted in a change of particle size distribution and polymorphic composition of the precipitate, in comparison to the reference systems. Thus, it was found that the supersatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…code: NH-V-UN and NH-V-UA). However, these findings do not agree with those from the previous study, in which ultrasonic treatment promotes an increase in the proportion of vaterite crystals [25] , [36] .…”
Section: Resultscontrasting
confidence: 99%
“…code: NH-V-UN and NH-V-UA). However, these findings do not agree with those from the previous study, in which ultrasonic treatment promotes an increase in the proportion of vaterite crystals [25] , [36] .…”
Section: Resultscontrasting
confidence: 99%
“…Thus, it can be concluded that, besides the adsorption, the calcite incorporates the Li + in the crystal structure, while vaterite particles can additionally entrap the Li-containing solution into the pores. Indeed, at the applied supersaturation level, vaterite spherulites are most probably formed by fast spherulitic growth, which is characterized exactly by the increased trapping of dissolved impurities, like Li + in this particular case [45,49,50].…”
Section: Synthesis and Characterization Of Thin Tabular {001} Calcitmentioning
confidence: 95%
“…However, a shortening of the induction time for vaterite formation, caused by applying more intensive agitation and seen as a pH drop, can be observed (ultrasonic < magnetic < mechanical). At that, the most likely mechanism of the promotion of nucleation in the case of sonication is a collapse of cavitation bubbles, which caused localized high pressure and temperature spots, while the literature data indicated that the energetic collisions among particles may enhance the transition of metastable vaterite to calcite as well [42][43][44][45]. In addition, the SEMs of the respective samples isolated after 5 days of aging ( Figure SI8) showed significantly different morphologies of calcite crystals.…”
Section: Synthesis and Characterization Of Thin Tabular {001} Calcitmentioning
confidence: 95%
“…An ultrasound irradiation technique has been applied to the formation of CaCO3 polymorphs (Price et al, 2011;Stoica-Guzun et al, 2012;Wagterveld et al, 2012;Njegić Džakula et al, 2014). The use of ultrasound can help control the crystallization process, and this is referred to as sonocrystallization (de Castro and PriegoCapote, 2007).…”
Section: Effect Of Other Factors On the Formation Of Caco3 Polymorphsmentioning
confidence: 99%